An application of fuzzy screening, fuzzy AHP and fuzzy Shannon's entropy on identification and prioritisation of effective factors in assessment of contractors in Fars Electric Power Distribution Company, Iran. (2017) - Mohamadi, Sahar; Ebrahimi, Abolghasem; Alimohammadlou, Moslem
Conducting assessment management and selecting the most efficient contractor are critical issues for efficiently implementing a project, using foreseen resources. Contractors' assessment significantly reduces the costs and improves corporate competitiveness. There are various techniques, including mathematical methods, used for assessing suppliers/contractors. Various qualitative and quantitative factors of different degrees of importance are involved in contractor assessment processes and must be considered before the decision-making phase. In this study, the effective factors were primarily identified using fuzzy screening method, and then the weights of criteria were measured through a combination of two methods, namely Fuzzy AHP and fuzzy Shannon's entropy. Findings revealed that the 'failures and accidents in previous projects' was the most important criteria in selecting contractors.